Functional biomaterials for corneal tissue regeneration - Venkateshwaran Krishnaswami; Jacob S.A. Jacob; Munish Kumar; Sivakumar Vijayaraghavalu (Biofunctional Materials)
The cornea, a pivotal component of the eye, plays a critical role in maintaining visual acuity through its mechanical strength and transparency. Approximately 90% of its thickness is derived from collagen lamellae, essential for its structural integrity. Alterations in corneal pathology, often resulting from injuries or age-related degeneration, significantly impair its function in light transmission and focusing, subsequently affecting visual quality. Traditional approaches to managing corneal diseases primarily include conservative therapies and donor tissue transplantation. However, these methods are frequently limited by risks of infection, rejection, and a scarcity of donor tissues. The inherent regenerative capabilities of corneal cells present a promising avenue for research into corneal tissue regeneration. Challenges such as inflammatory responses, neovascularization, and limbal stem cell deficiency pose significant threats to corneal clarity and function. The delicate balance between anti-angiogenic and proangiogenic factors is crucial. This review delves into the intricacies of corneal repair, examining the multitude of factors influencing this process. We provide an in-depth analysis of current advancements in corneal regeneration, highlighting the role of various functional biomaterials. These biomaterials, both synthetic and natural, offer innovative solutions for enhancing corneal regeneration, potentially revolutionizing the treatment of corneal diseases and injuries.